Hypothyroidism risk compared among nine common bipolar disorder therapies in a large US cohort. (May 2016) - Lambert, Christophe G; Mazurie, Aurélien J; Lauve, Nicolas R; Hurwitz, Nathaniel G; Young, S Stanley; Obenchain, Robert L; Hengartner, Nicolas W; Perkins, Douglas J; Tohen, Mauricio; Kerner, Berit
Abstract : Objectives: Thyroid abnormalities in patients with bipolar disorder (BD) have been linked to lithium treatment for decades, yet other drugs have been less well studied. Our objective was to compare hypothyroidism risk for lithium versus the anticonvulsants and second‐generation antipsychotics commonly prescribed for BD. Methods: Administrative claims data on 24, 574 patients with BD were analyzed with competing risk survival analysis. Inclusion criteria were (i) one year of no prior hypothyroid diagnosis nor BD drug treatment, (ii) followed by at least one thyroid test during BD monotherapy on lithium carbonate, mood‐stabilizing anticonvulsants (lamotrigine, valproate, oxcarbazepine, or carbamazepine) or antipsychotics (aripiprazole, olanzapine, risperidone, or quetiapine). The outcome was cumulative incidence of hypothyroidism per drug, in the presence of the competing risk of ending monotherapy, adjusted for age, sex, physician visits, and thyroid tests. Results: Adjusting for covariates, the four‐year cumulative risk of hypothyroidism for lithium (8.8%) was 1.39‐fold that of the lowest risk therapy, oxcarbazepine (6.3%). Lithium was non‐statistically significantly different from quetiapine. While lithium conferred a higher risk when compared to all other treatments combined as a group, hypothyroidism risk error bars overlapped for all drugs. Treatment (p = 3.86e‐3), age (p = 6.91e‐10), sex (p = 3.93e‐7), and thyroid testing (p = 2.79e‐87) affected risk. Patients taking lithium were tested for hypothyroidism 2.26–3.05 times more frequently than those on other treatments. Conclusions: Thyroid abnormalities occur frequently in patients with BD regardless of treatment. Therefore, patients should be regularly tested for clinical or subclinical thyroid abnormalities on all therapies and treated as indicated to prevent adverse effects of hormone imbalances on mood.